Efektivitas Ekstrak Etanol Buah Andaliman (Zanthoxylum acanthopodium DC) Sebagai Antibakteri Terhadap Escherichia coli - S, Mahral Effendi (Program Studi S1 Farmasi, STIKES Senior, Medan, 2022)
Zanthoxylum acanthopodium or Andaliman is a wild plant in North Sumatra, Indonesia that has been used as traditional medicine such as treating diarrhea, abdominal pain, dysentery, toothache, leprosy and abscesses. The purpose of this study was to determine the effect of andaliman fruit ethanol extract on the growth of Escherichia coli bacteria and to determine the effective concentration of andaliman fruit ethanol extract as an antibacterial causing diarrhea. The research method is experimental, which is carried out in stages. Extraction using the maceration method while the antibacterial activity test using the paper disc method. The extract concentration consisted of 70%, 50%, 30%, 10%, DMSO as a negative control and amoxicillin as a positive control. The phytochemical screening results consisted of alkaloids, flavonoids, saponins, tannins, steroids/triterpenoids. The results of the antibacterial activity test showed that the ethanolic extract of andaliman fruit had the potential as an antibacterial at each concentration respectively 70%, 50%, 30%, 10% with the diameter of the inhibition zones being 17.28 mm, 14.87 mm, 13.69 mm and 10.35 mm, respectively. strong category. The ethanol extract of andaliman fruit has an effective antibacterial activity at a concentration of 10%.